The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21037/atm.2017.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Peri-procedural antibiotic prophylaxis in ventricular septal defect: a case study to re-visit guidelines

Abstract: The current American Heart Association (AHA)/American College of Cardiology (ACC) guidelines do not recommend antibiotic prophylaxis for infective endocarditis (IE) in patients with acyanotic congenital valvular heart disease due to lack of any proven benefit and potential harm associated with antibiotics. As recognized by the guidelines, some acyanotic congenital heart disease, such as ventricular septal defects (VSDs), are associated with a high velocity jet and pose a greater risk of peri-procedural endocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Congenital heart defects are common in T21 (12%-60%). 25 CXL, being non-bacteremia inducing, does not warrant the systemic antibiotic prophylaxis recommended for invasive procedures in congenital heart defects 26 ; no systemic infections, particularly endocarditis, occurred postoperatively. Soeters et al 27 reported CXL under local anesthetic in T21; however, this is only appropriate for mild ID cases, and our data show GA to be safe in this population.…”
Section: Discussionmentioning
confidence: 98%
“…Congenital heart defects are common in T21 (12%-60%). 25 CXL, being non-bacteremia inducing, does not warrant the systemic antibiotic prophylaxis recommended for invasive procedures in congenital heart defects 26 ; no systemic infections, particularly endocarditis, occurred postoperatively. Soeters et al 27 reported CXL under local anesthetic in T21; however, this is only appropriate for mild ID cases, and our data show GA to be safe in this population.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately 70–80% of its energy derives from oxidative phosphorylation in mitochondria fueled by fatty acid–based oxidative phosphorylation. Conversely, in immature neonatal myocardium or iPSC-CMs, ATP production is predominately through the glycolytic pathway ( Sacchetto et al, 2019 ; Siasos et al, 2018 ). In previous studies, exposing iPSC-CMs to various clinically approved compounds with known cardiotoxicities led to a dose-dependent decrease in mitochondrial function in these cells ( Burridge et al, 2016 ; Rana et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al observed a substantially increased risk of IE in patients with VSD, reaching 1.90/1000 years, that is, 11‐15‐fold higher than in the general population, especially if unrepaired (1.90/1000 years) 3 . Even though antibiotic endocarditis prophylaxis is no longer recommended for patients with isolated uncorrected VSD, the presence of an increased risk of endocarditis is still debated 4 . The involvement of the right ventricle is very rare and has been reported in only five cases, all of them in adults, which is in contrast to the present case.…”
Section: Discussionmentioning
confidence: 99%